Root genomics - Oliveira, Antonio Costa de.; Varshney, R. K. (Rajeev K.) 1973-.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
With the predicted increase of the human population and the subsequent need for larger food supplies, root health in crop plants could play a major role in providing sustainable highly productive crops that can cope with global climate changes. While the essentiality of roots and their relation to plant performance is broadly recognized, less is known about the role of roots in plant growth and development. ?Root Genomics? examines how various new genomic technologies are rapidly being applied to the study of roots, including high-throughput sequencing and genotyping, TILLING, transcription factor analysis, comparative genomics, gene discovery and transcriptional profiling, post-transcriptional events regulating microRNAs, proteome profiling and the use of molecular markers such as SSRs, DArTs, and SNPs for QTL analyses and the identification of superior genes/alleles. The book also covers topics such as the molecular breeding of crops in problematic soils and the responses of root systems to a variety of stresses.
Introduction to root genomics -- EST-based approach for dissecting root architecture in barley using mutant traits of other species -- Genomics of Root-Microbe Interactions -- Plant genetics for study of the roles of root exudates and microbes in the soil -- Impact of the environment on root architecture in dicotyledoneous plants -- Mechanisms of aluminium tolerance -- Root responses to major abiotic stresses in flooded soils -- Genomics of root architecture and functions in maize -- Phenotyping for root traits and their improvement through biotechnological approaches to sustaining crop productivity -- Genomics and physiological approaches for root trait breeding to improve drought tolerance in chickpea (Cicer arietinum L.) -- Molecular breeding of cereals for aluminium resistance -- Molecular breeding of rice for problem soils.
Electronic reproduction.
Keywords: Roots (Botany) -- xGenetic aspects; Electronic books